Jerampah: Cultural Capital of the Sambas Malay Community in Supporting the Internalization of the Hospitality Values and Sustainable Tourism - Khosihan, Aan (GMPI Conference Series, 2022)
The balanced role of local communities in tourism development will arise in our minds when we discuss sustainable tourism. Dynamic tourism in Indonesia currently offers many strategic issues related to how to involve local communities to support its development, including adapting local values as an optimization strategy for Sapta Pesona Indonesia. On the other hand, local wisdom as cultural capital to support community resilience is very potential in maintaining the balance and sustainability of tourism development. This article aims to describe how the jerampah behavior in the Malay community of Sambas regency can be a potential cultural capital in supporting the internalization of the Sapta Pesona Indonesia program, especially for the hospitality value. A descriptive qualitative approach was used with the main data collection method in the form of interviews, observation, and analysis of secondary data obtained from news content on the tourism agenda in Temajuk Village and its surroundings from 2019 to 2020. It can be concluded that there is relevance between the jerampah behavior and the hospitality indicator in Sapta Pesona Indonesia. This cultural capital has also a social construction based on history. It is manifested in verbal and behavioral forms and relevant to be included in the internalization strategy of Sapta Pesona Indonesia based on local wisdom. Some Research by focusing on the internalization model of sapta pesona is needed for future research with similar themes.